Economic value of Maize (Zea mays L.) in Nigeria and its impacts on the global food production - Adiaha, Monday Sunday (International Journal of Scientific World, 2017)
The study surveys the economic value of Maize (Zea mays L) in Nigeria and its impact on global food production. The result analysis proves maize to be of high economic value in Nigeria, contributing massively to global increase in crop production. The crop has shown ability to be used in combating global food shortages. Data of this survey presented that production of maize in Nigeria has raised the standard of living, providing income to smallholder farmers and increased foreign exchange earnings. Utilization of maize in Nigeria ranges from; food, medicinal, pharmaceutical including industrial uses. Increase in maize production across Nigeria has greatly increase land utilization, where more arable land are been covered for the production of this important food crop, in-other to feed the ever-growing world population and as a measure for food/nutrition security, especially in developing countries like Nigeria.